'Grow the Scorched Ground Green': Values and Ethics in the Transition Movement. (12th August 2016) - Boudinot, F. Garrett; LeVasseur, Todd
Abstract : The Transition Movement is based on the premise that the dual threats of Peak Oil and anthropogenic climate change require humans to re-think and re-design how they live, with the focus becoming the creation of resilient, sustainable communities. The first Transition Town was created in Totnes, UK in 2005, and there are now Transition Towns worldwide. Using qualitative research methods, we explore the understudied affective, normative, and religio-ethical motivations of those engaged in the Transition Movement located in Totnes. Our research suggests that the Movement is guided by norms and ethics that are ecocentric, where nature is seen to be sacred and worthy of reverent care, and members can be classified as being part of a larger, emergent terrapolitan citizenry. We also briefly explore how the values and ethics of those in the Transition Movement trigger lifestyle changes which are more ecologically responsible than those offered by contemporary industrial societies.